Hakikat Metode dalam Pendidikan Islam - Darmiah Darmiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This method is the most appropriate way to determine the goal. Mastering the method will facilitate the path to achieving all goals, including Islamic education. In this case the method is a very important tool that can be used to achieve educational goals, so teachers need to understand the types of methods that support learning. The term method consists of two words, meta and hodos. Meta means pass and hodos means way. Therefore, this method can be understood as a path that must be taken to achieve a certain goal. In Al-Ghazali's view which is basically empirical, this is reflected in the desired way to emphasize the attitudes and behavior of educators in education, including: Teachers must love their students like their own children. Teachers do not expect a salary from their homework. Teachers should advise students to approach Allah SWT instead of studying for pride or personal gain. Teachers should encourage students to seek useful knowledge. Knowledge that can bring happiness in the hereafter is religious knowledge. The teacher must be a good example and a beautiful example in the eyes of students, just as children like to imitate their behavior.